Toward resilient cities: Mapping the interconnected factors shaping urbanization in a dual analysis framework - Naveed Ahmed; Wenlong Lou; Jameel Ahmed; Ali Akbar (PLoS ONE, 2025)
Utilizing the Push and Pull theory, this study examines the impact of socio-economic disparities and natural disasters on migration and urbanization. With a global significance, the shift of population from rural to urban areas carries profound implications for societies and economies. In the specific context of Pakistan, the research delves into the driving forces behind the rapid urbanization in Karachi and Quetta. Employing a mixed-methods approach, combining quantitative data and qualitative Geographic Information System (GIS) analysis, the study surveyed 1120 migrants. Results indicate a significant positive correlation between socio-economic disparities, natural disasters, and migration, highlighting the interplay of rural push factors and urban pull factors. GIS and satellite images reveal noticeable expansion in covered areas in both cities. The study underscores the importance of effective disaster management and resilient infrastructure to mitigate the impact of natural disasters on migration and urbanization. The findings offer valuable insights for policymakers and academics, discussed in the later sections of the study.